Beyond Meatless, the Health Effects of Vegan Diets: Findings from the Adventist Cohorts - Lap Tai Le (Nutrients, 2014)
Vegetarians, those who avoid meat, and vegans, additionally avoiding dairy and eggs, represent 5% and 2%, respectively, of the US population. The aim of this review is to assess the effects of vegetarian diets, particularly strict vegetarian diets (i.e., vegans) on health and disease outcomes. We summarized available evidence from three prospective cohorts of Adventists in North America: Adventist Mortality Study, Adventist Health Study, and Adventist Health Study-2. Non-vegetarian diets were compared to vegetarian dietary patterns (i.e., vegan and lacto-ovo-vegetarian) on selected health outcomes. Vegetarian diets confer protection against cardiovascular diseases, cardiometabolic risk factors, some cancers and total mortality. Compared to lacto-ovo-vegetarian diets, vegan diets seem to offer additional protection for obesity, hypertension, type-2 diabetes, and cardiovascular mortality. Males experience greater health benefits than females. Limited prospective data is available on vegetarian diets and body weight change. Large randomized intervention trials on the effects of vegetarian diet patterns on neurological and cognitive functions, obesity, diabetes, and other cardiovascular outcomes are warranted to make meaningful recommendations.